2012
DOI: 10.1155/2013/741953
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonication‐Induced Synthesis and Antimicrobial Evaluation of Some Multifluorinated Pyrazolone Derivatives

Abstract: A series of novel fluorine containing pyrazole-pyrazolone (4a–j) and chromone-pyrazolone (5a–i) was synthesized from multifluorinated pyrazolone by the Knoevenagel condensation reaction. All compounds were synthesized by conventional heating as well as ultrasound irradiation technique. It was found that ultrasonication method was more efficient than conventional heating method. The newly synthesized compounds were subjected forin vitroantimicrobial screening against four bacterial pathogens, namely,Staphylococ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Gadhave and colleagues [24] synthesized multi-fluorinated pyrazole-pyrazolone and chromone-pyrazolone compounds 21, 22, 23 and 24 ( Fig. 3) which exerted favorable antibacterial effects (Table 1), whereas all the compounds exhibited poor antifungal activity profile.…”
Section: Pyrazolones As Antimicrobial Agents and Their Sarmentioning
confidence: 99%
“…Gadhave and colleagues [24] synthesized multi-fluorinated pyrazole-pyrazolone and chromone-pyrazolone compounds 21, 22, 23 and 24 ( Fig. 3) which exerted favorable antibacterial effects (Table 1), whereas all the compounds exhibited poor antifungal activity profile.…”
Section: Pyrazolones As Antimicrobial Agents and Their Sarmentioning
confidence: 99%
“…Flavones are known for their antimicrobial 23 , antiviral 24 , anticancer 25 and antiinflammatory 26 properties. Literature data also revealed that chromones substituted with pyrazole nucleus exhibit antimicrobial 27,28 activities.…”
Section: Oriental Journal Of Chemistrymentioning
confidence: 96%
“…Gadhave et al [67] synthesized a series of novel fluorine-containing chromone-pyrazolone (64) and pyrazolepyrazolone (65) from multifluorinated pyrazolone by the Knoevenagel condensation reaction, used for the synthesis of diverse pharmaceutical products. All compounds were synthesized by conventional heating as well as ultrasound irradiation technique (Scheme 16).…”
Section: Pyrazolone Derivativesmentioning
confidence: 99%